Traditional Practices Regarding the Use of Botanicals to Treat Bovine Haemonchosis in Pakistan - Martinez-Salinas, J (CRC Press, 2023)
Haemonchus contortus, the causative agent of haemonchosis, is an intestinal nematode and commonly known as barber pole worm. It causes significant economic losses in small ruminants. In developing countries, it remains the major cause of impaired mutton and wool production and can lead to the death of animal. It is generally controlled by repeated treatment with anthelmintics, which increases the risk of residues in food and the development of drug resistance. Increasing anthelmintic resistance in the parasite has made it necessary to develop alternative ways of worm management and the use of botanicals has piqued interest in this approach, which has led to a global increase in the demand of medicinal plants for treating helminths and protozoa in small ruminants. Moreover, the traditional use of botanicals to treat Haemonchus in Pakistan has proved the effectiveness of the plants for this purpose. Nicotiana tabacum, Azadirachta indica, Allium sativum, Zingiber officinale, Curcurbita mexicana and Ficus religiosa are some botanicals known for their anthelminthic activity against Haemonchus. In essence, this chapter broadly discusses the anthelminthic activity of botanicals against bovine haemonchosis. © 2023 Taylor and Francis Group, LLC.